Pengaruh Penggunaan Media Papan Catur Edukatif Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV UPT SPF SD Negeri Kompleks IKIP 1 Kota Makassar - Hadawiatul Muafiq (CV. SINAR HOWUHOWU, 2026)
This research aims to determine the effect of using educational chessboard media on the critical thinking skills of fourth-grade students at UPT SPF SD Negeri Kompleks IKIP 1 Makassar. This study applied a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Pretest-Posttest Design. The research population consisted of all 444 fourth-grade students, with a sample of 72 students selected through cluster sampling. Class IV-A served as the experimental group (???? = 36), which received learning assisted by educational chessboard media, while Class IV-B served as the control group (???? = 36), which followed conventional learning methods. Data were collected using an essay test instrument based on Robert Ennis's critical thinking indicators, observation sheets for learning implementation, and documentation. Data analysis was performed using descriptive statistics and inferential statistics (Independent Sample T-Test) via IBM SPSS. The descriptive analysis results showed that the post-test mean score of the experimental class (84.03) was higher than that of the control class (65.92). Furthermore, the N-Gain analysis indicated that the experimental class achieved an average gain of 0.61 (medium category), whereas the control class only achieved 0.19 (low category). The hypothesis testing using the Independent Sample T-Test yielded a Sig. (2-tailed) value of 0.000, which is smaller than 0.05 (0.000 < 0.05). Consequently, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This study concludes that the use of educational chessboard media has a significant effect on improving the critical thinking skills of fourth-grade elementary school students.